Assessing the Use of Iron Oxide and Silica in Industrial Wastewater Treatment - Margaret Pascal Achola (Uganda Christian University, 2025)
Water pollution remains a crucial environmental challenge, associated with accelerated industrialization and urbanization. Industries generate substantial volumes of heavily polluted wastewater, posing serious risks to the ecosystems and human health. This highlights the critical need for effective wastewater treatment. This study assessed the use of iron oxide and silica in industrial wastewater treatment, focusing on the removal of pollutants such as COD, TSS, Turbidity, and total phosphorus. A batch adsorption experiment was conducted to evaluate the performance of the iron oxide under varying dosages and contact times. The results indicated removal efficiencies at a dosage of 50mg/l and a contact time of 60 minutes. The treated effluent exhibited significant reductions in pollutant concentrations, demonstrating the feasibility of using iron oxide and silica for industrial wastewater treatment. To advance these findings, further research is recommended to optimize the treatment system design. Additionally, the regeneration and reuse potential of silica for agricultural applications should be investigated to enhance its sustainability and environmental benefits.
Undergraduate